Self-repairable solid electrolyte and preparation method thereof

Through a preparation method of polymer electrolyte membrane, using specific amine compounds and diols and other materials, the problems of low safety and circulation performance of solid-state batteries are solved, high ionic conductivity and self-healing performance are achieved, and the safety and service life of the battery are significantly improved.

CN119601762APending Publication Date: 2025-03-11ZHEJIANG HUAYU NADIAN NEW ENERGY TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411754940.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

Solid-state batteries have low safety and circulation performance, and are prone to cracks, holes, defects and even direct rupture, resulting in short circuits of positive and negative electrodes, reducing the safety and service life of the battery.

Method used

A polymer electrolyte membrane is prepared by reacting isocyanate with an amine compound, diol, crosslinking agent and sodium salt are added, and the electrolyte prepolymer solution is finally added, and the polymer electrolyte membrane is obtained by casting and curing. This method uses materials such as 2,2'-bis(4-cyanophenoxy)benzidine and 1-dodecanoxy-2,4-phenylenediamine to improve the ionic conductivity and self-healing tensile properties of the electrolyte membrane.

Benefits of technology

The prepared polymer electrolyte membrane has high ionic conductivity and good self-repair tensile properties. When the battery is cycled for more than 1,000 times, the battery still maintains a capacity retention rate of more than 90%, which significantly improves the safety and service life of the solid-state battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119601762A_ABST
    Figure CN119601762A_ABST
Patent Text Reader

Abstract

The invention discloses a self-repairing solid electrolyte and a preparation method thereof, and belongs to the technical field of self-repairing solid electrolytes. The specific preparation method comprises the following steps: firstly, mixing isocyanate with an organic solvent, then adding an amine compound for reaction, then adding dihydric alcohol, a cross-linking agent and sodium salt for mixing, and finally adding a catalyst to obtain an electrolyte prepolymer solution; and pouring and curing the prepared electrolyte prepolymer solution to obtain the polymer electrolyte membrane. The polymer electrolyte membrane prepared by the invention has relatively high ionic conductivity and relatively good self-repairing tensile property, and a battery prepared by utilizing the polymer electrolyte membrane still has a capacity retention ratio of 90% or more after being cycled for 1000 times or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of self-repairing solid electrolytes, and in particular relates to a self-repairing solid electrolyte and a preparation method thereof. Background Art

[0002] Commercial sodium-ion batteries mostly use liquid electrolytes, which are prone to leakage, combustion and other problems. Using solid electrolytes to replace flammable organic liquid electrolytes can effectively improve the safety of batteries. Solid electrolytes are mainly divided into two categories: inorganic solid electrolytes and organic polymer-based electrolytes. Compared with inorganic solid electrolytes, organic polymer electrolytes have obvious advantages in cost, large-scale preparation, interface performance and mechanical flexibility, but there are still some problems that are difficult to solve. For example, polyethylene oxide (PEO) has been widely studied in polymer electrolytes because of its very good lithium salt solubility and high dielectric constant. However, PEO is a semi-crystalline polymer. Only the amorphous region can transport metal cations at room temperature. It has low ionic conductivity and weak mechanical properties at room temperature, which limits its further use. The electrolyte may produce cracks, holes, defects or even direct rupture during battery assembly or long-term cycling, resulting in a short circuit between the positive and negative electrodes, which will reduce the safety of solid-state batteries.

[0003] Self-healing materials have the ability to self-repair and utilize the external environment to repair themselves, and have a longer service life. Through molecular structure design, the self-healing function is introduced into the polymer electrolyte, which can repair internal damage to the electrolyte, thereby improving the safety and service life of the sodium ion battery. Patent CN109728342A self-healing polymer groups are selected from urea groups. The self-healing mechanism is that the urea groups are combined by hydrogen bonds to form a cross-linked structure. After the material is damaged, the cross-sections are contacted, and the material self-repair is achieved by hydrogen bonding. However, hydrogen bonding is a non-covalent bond that is weaker than covalent bonding, and the cross-linking effect and self-healing ability between hydrogen bonds are weaker than dynamic covalent bonds. Patent CN109659605A self-healing polyurethane is obtained by Diels-Alder reaction. The reversible action of the furan-maleimide structure in the polyurethane gives the polymer electrolyte good self-healing ability, but high temperature is required to activate and control its dynamic properties. Summary of the invention

[0004] The purpose of the present invention is to provide a self-repairable solid electrolyte and a preparation method to solve the problems of solid-state battery safety and low cycle performance.

[0005] In order to solve the above technical problems, the present invention specifically provides the following technical solutions: The present invention discloses a method for preparing a polymer electrolyte membrane, comprising: S1: First, isocyanate is mixed with an organic solvent and cooled, then an amine compound is added to react to obtain an oligourea solution, then a diol, a cross-linking agent and a sodium salt are added to the oligourea solution and mixed, and finally a catalyst is added to obtain an electrolyte prepolymer solution; the amine compound includes N,N'-di-tert-butylethylenediamine, 2,2'-bis(4-cyanophenoxy)benzidine and 1-dodecyloxy-2,4-phenylenediamine; 2,2'-bis(4-cyanophenoxy)benzidine is prepared by reacting m-nitrophenol with p-fluorobenzonitrile; the oligourea solution prepared using 2,2'-bis(4-cyanophenoxy)benzidine and 1-dodecyloxy-2,4-phenylenediamine has good compatibility between the polyurea soft segment and the hard segment, and has good thermal stability, thereby improving the ionic conductivity and self-healing tensile properties of the subsequently prepared polymer electrolyte membrane, as well as the cycle life of the battery prepared from the polymer electrolyte membrane.

[0006] S2: Casting and curing the electrolyte prepolymer solution prepared in S1 to obtain a polymer electrolyte membrane.

[0007] Preferably, the isocyanate is at least one of hexamethylene diisocyanate, isophorone diisocyanate, 1,4-cyclohexane diisocyanate, 1,4-cyclohexane dimethyl diisocyanate, and toluene diisocyanate; the organic solvent is acetone, and the usage ratio of isocyanate to organic solvent is 1 mol:50-65 ml.

[0008] Preferably, the molar ratio of the amine compound to the isocyanate is 1:0.18-5.5.

[0009] More preferably, the molar ratio of the amount of N,N'-di-tert-butylethylenediamine used to the amount of hexamethylene diisocyanate used is 1:2.5-3.5, the molar ratio of the amount of N,N'-di-tert-butylethylenediamine used to the amount of 2,2'-bis(4-cyanophenoxy)benzidine used is 1:0.19-0.45, and the molar ratio of the amount of N,N'-di-tert-butylethylenediamine used to the amount of 1-dodecyloxy-2,4-phenylenediamine used is 1:0.2-0.55.

[0010] Preferably, the diol is a polyether diol segmented by polysiloxane; the polyether diol segmented by polysiloxane is prepared from Si-H bond-terminated polysiloxane and polyethylene glycol monoallyl ether; the molar ratio of the amount of diol used to the amount of isocyanate used is 1:1.7-2.4.

[0011] Preferably, the cross-linking agent is triethanolamine, and the molar ratio of the amount of the cross-linking agent used to the amount of the isocyanate used is 1:6.8-7.9.

[0012] Preferably, the sodium salt is at least one of sodium hexafluorophosphate, sodium perchlorate, sodium bis(trifluoromethylsulfonyl)imide, sodium bis(fluorosulfonyl)imide, sodium bis(oxalatoborate) and sodium difluorooxalatoborate, and the mass fraction of the sodium salt in the electrolyte prepolymer solution is 21-29%.

[0013] Preferably, the catalyst is dibutyltin dilaurate, and the mass fraction of the catalyst in the electrolyte prepolymer solution is 0.15-0.5%.

[0014] Preferably, the cooling temperature in S1 is 0-5°C, and the reaction time after adding the amine compound is 1.5-2.5h; the mixing temperature after adding the diol, crosslinking agent and sodium salt is 23-27°C, and the mixing time is 0.8-1.2h.

[0015] Preferably, step S2 is carried out under nitrogen conditions, and the curing is first performed at 23-27° C. for 10-15 h, and then at 55-65° C. for 10-15 h.

[0016] The invention also discloses a battery, comprising the polymer electrolyte membrane prepared by the method.

[0017] The present invention discloses a method for preparing a polysiloxane-blocked polyether diol, which is specifically: Si-H bond terminated polysiloxane, polyethylene glycol monoallyl ether and toluene are mixed, heated to 70-80°C, then chloroplatinic acid-isopropanol solution is added, and then heated to 95-105°C for reaction for 10-20h to obtain polysiloxane-blocked polyether diol.

[0018] Preferably, the molar ratio of the amount of Si-H bond-terminated polysiloxane used to the amount of polyethylene glycol monoallyl ether used is 1:1-2.

[0019] Preferably, the mass ratio of the Si-H bond-terminated polysiloxane to toluene is 1:0.1-0.2.

[0020] Preferably, the chloroplatinic acid-isopropanol solution is obtained by adding chloroplatinic acid to isopropanol, and the amount of chloroplatinic acid added to isopropanol is 36-43 g / L.

[0021] Preferably, the mass ratio of the Si-H bond-terminated polysiloxane to the chloroplatinic acid-isopropanol solution is 1:0.002-0.004.

[0022] The present invention discloses a method for preparing 2,2'-bis(4-cyanophenoxy)benzidine, which specifically comprises: Add m-nitrophenol and zinc powder to ethanol and heat to 70-85°C, then drop sodium hydroxide solution to react for 5-10 hours, then rotary evaporation, purification separation, washing and drying to obtain an intermediate; add p-fluorobenzidine, potassium carbonate and N,N-dimethylacetamide to the intermediate, heat to 130-150°C, drop toluene to react for 3-5 hours, then heat to 140-155°C to react for 15-23 hours, and finally cool, precipitate, filter and dry to obtain the target product 2,2'-bis(4-cyanophenoxy)benzidine.

[0023] Preferably, the molar ratio of the amount of m-nitrophenol used to the amount of zinc powder used is 1:2900-3100.

[0024] Preferably, the sodium hydroxide solution added dropwise to the mixed solution is obtained by adding sodium hydroxide into water, the amount of sodium hydroxide added into water is 1 mol: 80-90 ml, and the amount ratio of m-nitrophenol to the sodium hydroxide solution is 1 mol: 580-620 ml.

[0025] Preferably, the molar ratio of the amount of the intermediate used to the amount of p-fluorobenzonitrile used is 1:1.8-2.2.

[0026] Preferably, the molar ratio of the amount of the intermediate used to the amount of potassium carbonate used is 1:2.2-2.7.

[0027] Preferably, the ratio of the intermediate to N,N-dimethylacetamide is 1 mol: 1.3-1.8 ml.

[0028] Preferably, the ratio of the intermediate to toluene is 1 mol: 0.8-1.3 ml.

[0029] Preferably, the reagents used for purification and separation are concentrated hydrochloric acid, sodium hydroxide solution and acetic acid. The sodium hydroxide solution is obtained by adding sodium hydroxide into water. The amount of sodium hydroxide added into water is 1 mol: 800-1200 ml.

[0030] More preferably, concentrated hydrochloric acid is first added during the purification and separation process, and the dosage ratio of m-nitrophenol to concentrated hydrochloric acid is 1 mol: 1100-1300 ml.

[0031] More preferably, the reaction time after adding concentrated hydrochloric acid is 8-12 hours.

[0032] More preferably, the pH is adjusted to 5-6 after adding acetic acid.

[0033] Preferably, the purification and separation temperature is 0-5°C.

[0034] Preferably, in the present invention, when preparing the electrolyte prepolymer solution, 1-[bis(2-hydroxyethyl)amino]-2-propanol can be used in addition to 2,2'-bis(4-cyanophenoxy)benzidine and 1-dodecyloxy-2,4-phenylenediamine. The coordinated use of 1-[bis(2-hydroxyethyl)amino]-2-propanol can form a stronger network polymer structure, improve physical properties such as hardness, tear and tensile strength, thereby further improving the ionic conductivity and self-healing tensile properties of the polymer electrolyte membrane, as well as the number of cycles of the battery prepared from the polymer electrolyte membrane.

[0035] More preferably, the molar ratio of the amount of 1-[bis(2-hydroxyethyl)amino]-2-propanol to the amount of hexamethylene diisocyanate is 1:8-16. Compared with the prior art, the present invention has the following beneficial effects: The present invention proposes a self-repairing solid electrolyte and a preparation method. First, isocyanate is mixed with an organic solvent, then an amine compound is added for reaction, then a diol, a cross-linking agent and a sodium salt are added for mixing, and finally a catalyst is added to obtain an electrolyte prepolymer solution; the prepared electrolyte prepolymer solution is cast and cured to obtain a polymer electrolyte membrane. The polymer electrolyte membrane prepared by the present invention has high ionic conductivity and good self-repairing tensile properties, and the battery prepared using the polymer electrolyte membrane has a capacity retention rate of more than 90% after more than 1,000 cycles. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] In order to more clearly illustrate the implementation methods of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for the implementation methods or the description of the prior art. Obviously, the drawings in the following description are only exemplary, and for ordinary technicians in this field, other implementation drawings can be derived from the provided drawings without creative work.

[0037] Figure 1 Graph showing the tensile properties under different self-repairing conditions. DETAILED DESCRIPTION

[0038] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0039] The following first describes the concepts involved in the present application in conjunction with the accompanying drawings. It should be noted that the following description of each concept is only to make the content of the present application easier to understand, and does not limit the scope of protection of the present application; at the same time, the embodiments and features in the embodiments of the present application can be combined with each other in the absence of conflict. The present application will be described in detail with reference to the accompanying drawings and in conjunction with the embodiments.

[0040] Embodiment 1: Preparation of polysiloxane-blocked polyether diol: Si-H bond-terminated polysiloxane, polyethylene glycol monoallyl ether and toluene are mixed, heated to 75°C, and then chloroplatinic acid-isopropanol solution is added, and then heated to 100°C for reaction for 15 hours to obtain polysiloxane-blocked polyether diol. The molar ratio of the amount of Si-H bond-terminated polysiloxane to the amount of polyethylene glycol monoallyl ether is 1:2, the mass ratio of the amount of Si-H bond-terminated polysiloxane to the amount of toluene is 1:0.15, the chloroplatinic acid-isopropanol solution is obtained by adding chloroplatinic acid to isopropanol, the amount of chloroplatinic acid added to isopropanol is 40.98 g / L, and the mass ratio of the amount of Si-H bond-terminated polysiloxane to the amount of chloroplatinic acid-isopropanol solution is 1:0.003.

[0041] Preparation of electrolyte prepolymer solution: Hexamethylene diisocyanate and acetone were mixed to obtain a mixed solution, which was cooled to 4°C, and then N,N'-di-tert-butylethylenediamine was added to the mixed solution, and the reaction was continued for 2 hours to obtain a low-polyurea solution. After the reaction was completed, polysiloxane-blocked polyether diol, triethanolamine and sodium bis(trifluoromethylsulfonyl)imide were added to the low-polyurea solution at 25°C and mixed for 1 hour, and then dibutyltin dilaurate was added to obtain an electrolyte prepolymer solution. The usage ratio of hexamethylene diisocyanate and acetone is 1 mol:55 ml, the molar ratio of N,N'-di-tert-butylethylenediamine to hexamethylene diisocyanate is 1:3, the molar ratio of polysiloxane-blocked polyether diol to hexamethylene diisocyanate is 1:2, the molar ratio of triethanolamine to hexamethylene diisocyanate is 1:7.5, the mass fraction of sodium bis(trifluoromethylsulfonyl)imide in the electrolyte prepolymer solution is 25%, and the mass fraction of dibutyltin dilaurate in the electrolyte prepolymer solution is 0.3%.

[0042] Preparation of polymer electrolyte membrane: The electrolyte prepolymer solution was poured into a mold, and cured at 25°C for 12 h under nitrogen conditions, and then cured at 60°C for 12 h to obtain a polymer electrolyte membrane.

[0043] Embodiment 2: The preparation of polysiloxane-blocked polyether diol is the same as in Example 1.

[0044] Preparation of electrolyte prepolymer solution: The preparation of the electrolyte prepolymer solution in this embodiment is compared with that in Example 1, except that the molar ratio of the amount of polysiloxane-blocked polyether diol used to the amount of hexamethylene diisocyanate used is 1:1.8, and other conditions and parameters are the same as in Example 1.

[0045] The preparation of the polymer electrolyte membrane is the same as in Example 1.

[0046] Embodiment 3: The preparation of polysiloxane-blocked polyether diol is the same as in Example 1.

[0047] Preparation of electrolyte prepolymer solution: The preparation of the electrolyte prepolymer solution in this embodiment is compared with that in Example 1, except that the molar ratio of the amount of N,N'-di-tert-butylethylenediamine used to the amount of hexamethylene diisocyanate used is 1:2, and the molar ratio of the amount of polysiloxane-blocked polyether diol used to the amount of hexamethylene diisocyanate used is 1:2.5. Other conditions and parameters are the same as in Example 1.

[0048] The preparation of the polymer electrolyte membrane is the same as in Example 1.

[0049] Embodiment 4: The preparation of polysiloxane-blocked polyether diol is the same as in Example 1.

[0050] Preparation of electrolyte prepolymer solution: The preparation of the electrolyte prepolymer solution in this embodiment is compared with that in Example 1, except that the molar ratio of the amount of N,N'-di-tert-butylethylenediamine used to the amount of hexamethylene diisocyanate used is 1:4, and the molar ratio of the amount of polysiloxane-blocked polyether diol used to the amount of hexamethylene diisocyanate used is 1:1.5. Other conditions and parameters are the same as in Example 1.

[0051] The preparation of the polymer electrolyte membrane is the same as in Example 1.

[0052] Embodiment 5: The preparation of polysiloxane-blocked polyether diol is the same as in Example 1.

[0053] Preparation of electrolyte prepolymer solution: The preparation of the electrolyte prepolymer solution in this embodiment is compared with that in Example 1, except that the molar ratio of the amount of N,N'-di-tert-butylethylenediamine used to the amount of hexamethylene diisocyanate used is 1:4, and the molar ratio of the amount of polysiloxane-blocked polyether diol used to the amount of hexamethylene diisocyanate used is 1:1.9. Other conditions and parameters are the same as in Example 1.

[0054] The preparation of the polymer electrolyte membrane is the same as in Example 1.

[0055] Embodiment 6: The preparation of polysiloxane-blocked polyether diol is the same as in Example 1.

[0056] Preparation of 2,2'-bis(4-cyanophenoxy)benzidine: m-nitrophenol and zinc powder are added to ethanol to obtain a mixed solution, then heated to 75°C, and then sodium hydroxide solution is added dropwise to the mixed solution for continuous reaction for 8 hours. After the reaction, a mixed product is obtained by rotary evaporation, and then the temperature is lowered to 4°C, and concentrated hydrochloric acid is added to the mixed product for continuous reaction for 10 hours. After the reaction, the filter cake is filtered to obtain a filter cake, which is dissolved in sodium hydroxide solution, and then acetic acid is added to adjust the pH to 5.5 to separate the solid, which is washed and dried to obtain an intermediate. p-Fluorobenzyl cyanide, potassium carbonate and N,N-dimethylacetamide are added to the intermediate to obtain a dissolving solution, which is heated to 135°C, and then toluene is added dropwise to the dissolving solution for continuous reaction for 3.5 hours, and then the temperature is raised to 150°C for reaction for 18 hours to obtain a product solution, which is cooled to 25°C and water is added to precipitate the solid, which is then filtered, washed and dried to obtain 2,2'-bis(4-cyanophenoxy)benzidine. The molar ratio of the amount of m-nitrophenol to the amount of zinc powder is 1:3000, the sodium hydroxide solution added dropwise to the mixed solution is obtained by adding sodium hydroxide into water, and the amount of sodium hydroxide added into water is 1 mol:83.33 ml, the amount ratio of m-nitrophenol to the sodium hydroxide solution is 1 mol:600 ml, the amount ratio of m-nitrophenol to concentrated hydrochloric acid is 1 mol:1200 ml, the sodium hydroxide solution used to dissolve the filter cake is obtained by adding sodium hydroxide into water, and the amount of sodium hydroxide added into water is 1 mol:1000 ml, the molar ratio of the amount of the intermediate to the amount of p-fluorobenzamide is 1:2, the molar ratio of the amount of the intermediate to the amount of potassium carbonate is 1:2.5, the amount ratio of the intermediate to N,N-dimethylacetamide is 1 mol:1.5 ml, and the amount ratio of the intermediate to toluene is 1 mol:1 ml.

[0057] Preparation of electrolyte prepolymer solution: Hexamethylene diisocyanate and acetone were mixed to obtain a mixed solution, which was cooled to 4°C, and then N,N'-di-tert-butylethylenediamine, 2,2'-bis(4-cyanophenoxy)benzidine and 1-dodecyloxy-2,4-phenylenediamine were added to the mixed solution, and the reaction was continued for 2 hours to obtain a low-polyurea solution. After the reaction was completed, polysiloxane-blocked polyether diol, triethanolamine and sodium bis(trifluoromethylsulfonyl)imide were added to the low-polyurea solution at 25°C and mixed for 1 hour, and then dibutyltin dilaurate was added to obtain an electrolyte prepolymer solution. The dosage ratio of hexamethylene diisocyanate to acetone is 1 mol:55 ml, the molar ratio of N,N'-di-tert-butylethylenediamine to hexamethylene diisocyanate is 1:3, the molar ratio of N,N'-di-tert-butylethylenediamine to 2,2'-bis(4-cyanophenoxy)benzidine is 1:0.2, the molar ratio of N,N'-di-tert-butylethylenediamine to 1-dodecyloxy-2,4-phenylenediamine is 1:0.3, the molar ratio of polysiloxane-blocked polyether diol to hexamethylene diisocyanate is 1:2, the molar ratio of triethanolamine to hexamethylene diisocyanate is 1:7.5, the mass fraction of sodium bis(trifluoromethylsulfonyl)imide in the electrolyte prepolymer solution is 25%, and the mass fraction of dibutyltin dilaurate in the electrolyte prepolymer solution is 0.3%.

[0058] Preparation of polymer electrolyte membrane: The preparation of the polymer electrolyte membrane in this embodiment is different from that in Example 1, except that the electrolyte prepolymer solution used is the electrolyte prepolymer solution prepared in this embodiment, and other conditions and parameters are the same as in Example 1.

[0059] Embodiment 7: The preparation of polysiloxane-blocked polyether diol is the same as in Example 1.

[0060] The preparation of 2,2'-bis(4-cyanophenoxy)benzidine was the same as in Example 6.

[0061] Preparation of electrolyte prepolymer solution: The preparation of the electrolyte prepolymer solution in this embodiment is compared with that in Example 6, except that the molar ratio of the amount of N,N'-di-tert-butylethylenediamine used to the amount of 2,2'-bis(4-cyanophenoxy)benzidine used is 1:0.35, and the other conditions and parameters are the same as in Example 6.

[0062] Preparation of polymer electrolyte membrane: The preparation of the polymer electrolyte membrane in this embodiment is different from that in Example 1, except that the electrolyte prepolymer solution used is the electrolyte prepolymer solution prepared in this embodiment, and other conditions and parameters are the same as in Example 1.

[0063] Embodiment 8: The preparation of polysiloxane-blocked polyether diol is the same as in Example 1.

[0064] The preparation of 2,2'-bis(4-cyanophenoxy)benzidine was the same as in Example 6.

[0065] Preparation of electrolyte prepolymer solution: The preparation of the electrolyte prepolymer solution in this embodiment is compared with that in Example 6, except that the molar ratio of the amount of N,N'-di-tert-butylethylenediamine used to the amount of 1-dodecyloxy-2,4-phenylenediamine used is 1:0.45, and the other conditions and parameters are the same as in Example 6.

[0066] Preparation of polymer electrolyte membrane: The preparation of the polymer electrolyte membrane in this embodiment is different from that in Example 1, except that the electrolyte prepolymer solution used is the electrolyte prepolymer solution prepared in this embodiment, and other conditions and parameters are the same as in Example 1.

[0067] Embodiment 9: The preparation of polysiloxane-blocked polyether diol is the same as in Example 1.

[0068] The preparation of 2,2'-bis(4-cyanophenoxy)benzidine was the same as in Example 6.

[0069] Preparation of electrolyte prepolymer solution: Hexamethylene diisocyanate and acetone were mixed to obtain a mixed solution, which was cooled to 4°C, and then N,N'-di-tert-butylethylenediamine, 2,2'-bis(4-cyanophenoxy)benzidine and 1-dodecyloxy-2,4-phenylenediamine were added to the mixed solution, and the reaction was continued for 2 hours to obtain a low-polyurea solution. After the reaction was completed, polysiloxane-blocked polyether diol, triethanolamine, 1-[bis(2-hydroxyethyl)amino]-2-propanol and sodium bis(trifluoromethylsulfonyl)imide were added to the low-polyurea solution at 25°C and mixed for 1 hour, and then dibutyltin dilaurate was added to obtain an electrolyte prepolymer solution. The molar ratio of hexamethylene diisocyanate to acetone is 1 mol:55 ml, the molar ratio of N,N'-di-tert-butylethylenediamine to hexamethylene diisocyanate is 1:3, and the molar ratio of N,N'-di-tert-butylethylenediamine to 2,2'-bis(4 The molar ratio of the amount of N,N'-di-tert-butylethylenediamine to the amount of 1-dodecyloxy-2,4-phenylenediamine is 1:0.3, the molar ratio of the amount of polysiloxane-blocked polyether diol to the amount of hexamethylene diisocyanate is 1:2, the molar ratio of the amount of triethanolamine to the amount of hexamethylene diisocyanate is 1:7.5, the molar ratio of the amount of 1-[bis(2-hydroxyethyl)amino]-2-propanol to the amount of hexamethylene diisocyanate is 1:15, the mass fraction of sodium bis(trifluoromethylsulfonyl)imide in the electrolyte prepolymer solution is 25%, and the mass fraction of dibutyltin dilaurate in the electrolyte prepolymer solution is 0.3%.

[0070] Preparation of polymer electrolyte membrane: The preparation of the polymer electrolyte membrane in this embodiment is different from that in Example 1, except that the electrolyte prepolymer solution used is the electrolyte prepolymer solution prepared in this embodiment, and other conditions and parameters are the same as in Example 1.

[0071] Embodiment 10: The preparation of polysiloxane-blocked polyether diol is the same as in Example 1.

[0072] The preparation of 2,2'-bis(4-cyanophenoxy)benzidine was the same as in Example 2.

[0073] Preparation of electrolyte prepolymer solution: The preparation of the electrolyte prepolymer solution in this embodiment is compared with that in Example 9, except that the molar ratio of the amount of 1-[bis(2-hydroxyethyl)amino]-2-propanol used to the amount of hexamethylene diisocyanate used is 1:12, and other conditions and parameters are the same as in Example 9.

[0074] Preparation of polymer electrolyte membrane: The preparation of the polymer electrolyte membrane in this embodiment is different from that in Example 1, except that the electrolyte prepolymer solution used is the electrolyte prepolymer solution prepared in this embodiment, and other conditions and parameters are the same as in Example 1.

[0075] Comparative Example 1: The preparation of polysiloxane-blocked polyether diol is the same as in Example 1.

[0076] Preparation of electrolyte prepolymer solution: The preparation of the electrolyte prepolymer solution in this example is different from that in Example 6, except that 2,2'-bis(4-cyanophenoxy)benzidine is not used in this example, and other conditions and parameters are the same as those in Example 6.

[0077] Preparation of polymer electrolyte membrane: The preparation of the polymer electrolyte membrane in this embodiment is different from that in Example 1, except that the electrolyte prepolymer solution used is the electrolyte prepolymer solution prepared in this embodiment, and other conditions and parameters are the same as in Example 1.

[0078] Comparative Example 2: The preparation of polysiloxane-blocked polyether diol is the same as in Example 1.

[0079] The preparation of 2,2'-bis(4-cyanophenoxy)benzidine was the same as in Example 6.

[0080] Preparation of electrolyte prepolymer solution: The preparation of the electrolyte prepolymer solution in this embodiment is compared with that in Example 6, except that 1-dodecyloxy-2,4-phenylenediamine is not used in this embodiment, and other conditions and parameters are the same as in Example 6.

[0081] Preparation of polymer electrolyte membrane: The preparation of the polymer electrolyte membrane in this embodiment is different from that in Example 1, except that the electrolyte prepolymer solution used is the electrolyte prepolymer solution prepared in this embodiment, and other conditions and parameters are the same as in Example 1.

[0082] Experimental Example 1: Determination of ionic conductivity: The ionic conductivity of the polymer electrolyte membranes prepared in Examples 1-10 and Comparative Examples 1-2 was measured by AC impedance method.

[0083] Table 1 Ionic conductivity measurement results

[0084] The results are shown in Table 1. Compared with Example 6, the ionic conductivity of the polymer electrolyte membrane prepared in Example 1 is lower than that in Example 6, indicating that the use of 2,2'-bis(4-cyanophenoxy)benzidine and 1-dodecyloxy-2,4-phenylenediamine can improve the ionic conductivity of the polymer electrolyte membrane; compared with Examples 7 and 8, Example 6 shows that increasing the amount of 2,2'-bis(4-cyanophenoxy)benzidine and 1-dodecyloxy-2,4-phenylenediamine within a certain range can improve the ionic conductivity of the polymer electrolyte membrane; compared with Example 9, Example 6 shows that when using 2,2'-bis(4 On the basis of 2,2'-bis(4-cyanophenoxy)benzidine and 1-dodecyloxy-2,4-phenylenediamine, 1-[bis(2-hydroxyethyl)amino]-2-propanol is used to further improve the ionic conductivity of the polymer electrolyte membrane; compared with Example 10, Example 9 shows that increasing the amount of 1-[bis(2-hydroxyethyl)amino]-2-propanol used within a certain range can improve the ionic conductivity of the polymer electrolyte membrane; compared with Comparative Examples 1 and 2, Example 6 shows that 2,2'-bis(4-cyanophenoxy)benzidine and 1-dodecyloxy-2,4-phenylenediamine need to be used together, and using either 2,2'-bis(4-cyanophenoxy)benzidine or 1-dodecyloxy-2,4-phenylenediamine alone has no obvious effect on improving the ionic conductivity of the polymer electrolyte membrane.

[0085] Experimental Example 2: The tensile properties under different self-repairing conditions were first measured for the original tensile strength and tensile fracture strain of the polymer electrolyte membrane prepared in Example 1, and then the polymer electrolyte membrane was cut into two sections, and then cured, the polymer electrolyte membrane could self-repair, and the tensile strength and fracture strain were measured again after repair, and the tensile strength recovery rate and fracture strain recovery rate were obtained by comparing with the initial tensile strength and fracture strain. The measurement method was the same as that of Experimental Example 2, where the curing conditions were fixed at 25°C for 12h; cured at 38°C for 1h; cured at 38°C for 6h; and cured at 38°C for 12h.

[0086] like Figure 1As shown in the figure, the original tensile strength is 14.6MPa and the tensile fracture strain is 708%, indicating that the electrolyte membrane has good mechanical properties and excellent flexibility; after curing at 25℃ for 12h, it can self-repair, with a tensile fracture strain recovery rate of 50% and a tensile strength recovery rate of 57%; at 38℃, the polymer electrolyte membrane shows faster and better self-healing performance, and the longer the curing time, the stronger the self-healing ability of the material. After curing at 38℃ for 1h, the tensile strength recovery rate is 48%, and the tensile fracture strain recovery rate is 55%; after curing at 38℃ for 6h, the tensile strength recovery rate is 70%, and the tensile fracture strain recovery rate is 70%; after curing at 38℃ for 12 hours, the tensile strength recovery rate is 89%, and the tensile fracture strain recovery rate is 85%.

[0087] Experimental Example 3: Self-repairing tensile performance measurement: The self-repairing tensile performance of the polymer electrolyte membranes prepared in Examples 1-10 and Comparative Examples 1-2 was measured in the same manner as in Experimental Example 2. The curing condition was 38° C. for 12 h.

[0088] Table 2 Self-repairing tensile properties test results

[0089] The results are shown in Table 2. Compared with Example 6, the original tensile strength, original tensile fracture strain, tensile strength recovery rate and tensile fracture strain recovery rate of the polymer electrolyte membrane prepared in Example 1 are all lower than those in Example 6, indicating that the use of 2,2'-bis(4-cyanophenoxy)benzidine and 1-dodecyloxy-2,4-phenylenediamine can improve the self-repairing tensile properties of the polymer electrolyte membrane; compared with Examples 7 and 8, Example 6 shows that the increase in the amount of 2,2'-bis(4-cyanophenoxy)benzidine and 1-dodecyloxy-2,4-phenylenediamine within a certain range can improve the self-repairing tensile properties of the polymer electrolyte membrane; compared with Example 9, Example 6 shows that when using 2,2'-bis(4 On the basis of 2,2'-bis(4-cyanophenoxy)benzidine and 1-dodecyloxy-2,4-phenylenediamine, 1-[bis(2-hydroxyethyl)amino]-2-propanol is used to further improve the self-repairing tensile properties of the polymer electrolyte membrane; Example 9 is compared with Example 10, indicating that the increase in the amount of 1-[bis(2-hydroxyethyl)amino]-2-propanol used within a certain range can improve the self-repairing tensile properties of the polymer electrolyte membrane; Example 6 is compared with Comparative Examples 1 and 2, indicating that 2,2'-bis(4-cyanophenoxy)benzidine and 1-dodecyloxy-2,4-phenylenediamine need to be used together, and the use of any one of 2,2'-bis(4-cyanophenoxy)benzidine and 1-dodecyloxy-2,4-phenylenediamine alone has no obvious effect on improving the self-repairing tensile properties of the polymer electrolyte membrane.

[0090] Experimental Example 3: Determination of the number of cycles: The electrolyte prepolymer solution prepared in Examples 1-10 and Comparative Examples 1-2 was injected into the packaged soft-pack sodium ion dry battery cell and placed at 25°C for 24 hours to allow the electrolyte prepolymer solution to fully infiltrate the pole piece and the separator. The battery was cured at 0.5Mpa and 60°C for 12 hours to obtain a solid-state sodium ion battery. The number of cycles of the solid-state sodium ion battery with a capacity retention rate of ≥90% at 25°C and 1C was determined.

[0091] Table 3 Results of determination of the number of cycles

[0092] The results are shown in Table 3. Compared with Example 6, the number of cycles of the solid-state sodium ion battery made of the polymer electrolyte membrane prepared in Example 1 is lower than that in Example 6, indicating that the use of 2,2'-bis(4-cyanophenoxy)benzidine and 1-dodecyloxy-2,4-phenylenediamine can improve the number of cycles, i.e., the cycle performance, of the solid-state sodium ion battery made of the polymer electrolyte membrane; compared with Examples 7 and 8, Example 6 shows that increasing the amount of 2,2'-bis(4-cyanophenoxy)benzidine and 1-dodecyloxy-2,4-phenylenediamine within a certain range can improve the number of cycles of the solid-state sodium ion battery made of the polymer electrolyte membrane; compared with Example 9, Example 6 shows that when using 2,2'-bis(4 -cyanophenoxy) benzidine and 1-dodecyloxy-2,4-phenylenediamine, 1-[bis(2-hydroxyethyl)amino]-2-propanol is used to further improve the number of cycles of the solid-state sodium ion battery made of the polymer electrolyte membrane; Example 9 is compared with Example 10, indicating that the increase in the amount of 1-[bis(2-hydroxyethyl)amino]-2-propanol used within a certain range can improve the number of cycles of the solid-state sodium ion battery made of the polymer electrolyte membrane; Example 6 is compared with Comparative Examples 1 and 2, indicating that 2,2'-bis(4-cyanophenoxy) benzidine and 1-dodecyloxy-2,4-phenylenediamine need to be used together, and the use of any one of 2,2'-bis(4-cyanophenoxy) benzidine and 1-dodecyloxy-2,4-phenylenediamine alone has no obvious effect on improving the cycle performance of the solid-state sodium ion battery made of the polymer electrolyte membrane.

[0093] The embodiments and / or implementation methods described above are only used to illustrate the preferred embodiments and / or implementation methods for realizing the technology of the present invention, and are not intended to limit the implementation methods of the technology of the present invention in any form. Any technical personnel in this field may make slight changes or modifications to other equivalent embodiments without departing from the scope of the technical means disclosed in the content of the present invention, but they should still be regarded as technologies or embodiments that are essentially the same as the present invention.

[0094] This article uses specific examples to illustrate the principles and implementation methods of this application. The description of the above embodiments is only used to help understand the method and its core ideas of this application. The above is only the preferred implementation method of this application. It should be pointed out that due to the limitations of textual expression and the objective existence of infinite specific structures, ordinary technicians in this technical field can make several improvements, modifications or changes without departing from the principles of this application, and can also combine the above technical features in an appropriate manner; these improvements, modifications, changes or combinations, or the direct application of the concept and technical solution of the invention to other occasions without improvement, should be regarded as the scope of protection of this application.

Claims

1. A method for preparing a polymer electrolyte membrane, comprising: S1: firstly, isocyanate is mixed with an organic solvent and cooled, then an amine compound is added to react to obtain a low-polyurea solution, then a diol, a cross-linking agent and a sodium salt are added to the low-polyurea solution for mixing, and finally a catalyst is added to obtain an electrolyte prepolymer solution; the amine compound includes N,N'-di-tert-butylethylenediamine, 2,2'-bis(4-cyanophenoxy)benzidine and 1-dodecyloxy-2,4-phenylenediamine; 2,2'-bis(4-cyanophenoxy)benzidine is prepared by reacting m-nitrophenol with p-fluorobenzonitrile; S2: Casting and curing the electrolyte prepolymer solution prepared in S1 to obtain a polymer electrolyte membrane.

2. The method for preparing a polymer electrolyte membrane according to claim 1, characterized in that: The isocyanate is at least one of hexamethylene diisocyanate, isophorone diisocyanate, 1,4-cyclohexane diisocyanate, 1,4-cyclohexane dimethyl diisocyanate and toluene diisocyanate; the organic solvent is acetone, and the dosage ratio of the isocyanate to the organic solvent is 1 mol: 50-65 ml.

3. The method for preparing a polymer electrolyte membrane according to claim 1, characterized in that: The molar ratio of the amine compound to the isocyanate is 1:0.18-5.

5.

4. The method for preparing a polymer electrolyte membrane according to claim 1, characterized in that: The diol is a polyether diol segmented by polysiloxane; the polyether diol segmented by polysiloxane is prepared from polysiloxane terminated by Si-H bonds and polyethylene glycol monoallyl ether; the molar ratio of the amount of diol used to the amount of isocyanate used is 1:1.7-2.

4.

5. The method for preparing a polymer electrolyte membrane according to claim 1, characterized in that: The cross-linking agent is triethanolamine, and the molar ratio of the amount of the cross-linking agent used to the amount of the isocyanate used is 1:6.8-7.

9.

6. The method for preparing a polymer electrolyte membrane according to claim 1, characterized in that: The sodium salt is at least one of sodium hexafluorophosphate, sodium perchlorate, sodium bis(trifluoromethylsulfonyl)imide, sodium bis(fluorosulfonyl)imide, sodium bis(oxalatoborate) and sodium difluorooxalatoborate, and the mass fraction of the sodium salt in the electrolyte prepolymer solution is 21-29%.

7. The method for preparing a polymer electrolyte membrane according to claim 1, characterized in that: The catalyst is dibutyltin dilaurate, and the mass fraction of the catalyst in the electrolyte prepolymer solution is 0.15-0.5%.

8. The method for preparing a polymer electrolyte membrane according to claim 1, characterized in that: In the S1, the cooling temperature is 0-5°C, and the reaction time after adding the amine compound is 1.5-2.5h; after adding the diol, the crosslinking agent and the sodium salt, the mixing temperature is 23-27°C, and the mixing time is 0.8-1.2h.

9. The method for preparing a polymer electrolyte membrane according to claim 1, characterized in that: The S2 step is carried out under nitrogen conditions, and the curing is first performed at 23-27° C. for 10-15 h, and then at 55-65° C. for 10-15 h.

10. A battery comprising a polymer electrolyte membrane prepared by the method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Self-repairing polymer electrolyte matrix and preparation method thereof, self-repairing polymer electrolyte, lithium ion battery and application thereof

    CN109659605A

  • Self-repairing composite solid electrolyte, quasi-solid electrolyte and lithium battery

    CN109728342A